2021
DOI: 10.1007/s12542-021-00594-3
|View full text |Cite
|
Sign up to set email alerts
|

A relict oasis of living deep-sea mussels Bathymodiolus and microbial-mediated seep carbonates at newly-discovered active cold seeps in the Gulf of Cádiz, NE Atlantic Ocean

Abstract: Extensive beds of the deep-sea mussel Bathymodiolus mauritanicus (currently also known as Gigantidas mauritanicus) linked to active cold seeps related to fissure-like activity on Al Gacel mud volcano, Gulf of Cádiz, were filmed and sampled for the first time during the oceanographic expedition SUBVENT-2 aboard R/V Sarmiento de Gamboa. Al Gacel mud volcano is one of up to 80 fluid venting submarine structures (mud volcanoes and mud volcano/diapir complexes) identified in the Gulf of Cádiz as result of explosive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Here, we present an overview of different chemosynthetic biomineralization processes that occur in syntrophic relationships between microbial organisms or even between microorganisms and associated major fauna. In mud volcanoes from the Gulf of Cádiz we observed anaerobic oxidation of methane (AOM), and sulfur-oxidation and methane oxidation driven in symbiosis with Bathymodiolus mussels and Siboglinidae worms (Rincón-Tomás et al, 2019;Somoza et al, 2021). In a recently discovered shallowwater low-temperature hydrothermal system in the Tagoro Volcano (Canary Islands), we detected biogenic Fe-oxyhydroxides and sulfur-oxidizing bacterial mats (González et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…Here, we present an overview of different chemosynthetic biomineralization processes that occur in syntrophic relationships between microbial organisms or even between microorganisms and associated major fauna. In mud volcanoes from the Gulf of Cádiz we observed anaerobic oxidation of methane (AOM), and sulfur-oxidation and methane oxidation driven in symbiosis with Bathymodiolus mussels and Siboglinidae worms (Rincón-Tomás et al, 2019;Somoza et al, 2021). In a recently discovered shallowwater low-temperature hydrothermal system in the Tagoro Volcano (Canary Islands), we detected biogenic Fe-oxyhydroxides and sulfur-oxidizing bacterial mats (González et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…Since the first discovery (Paull et al., 1984), cold seeps received extensive research attention due to their close association with gas hydrate, petroleum, and diverse seep‐endemic micro‐/macro‐faunas (e.g., Boetius & Wenzhöfer, 2013; Cordes et al., 2009; Feng et al., 2018; Hu et al., 2019; Judd, 2003; Naudts et al., 2006, 2010; Netzeband et al., 2010; Rincón‐Tomas et al., 2019, 2020; Römer et al., 2012; Somoza et al., 2021a; Suess, 2014; Suess et al., 1999). They also contribute substantially to the global carbon cycle, given the abundant hydrocarbon reservoir and leakage beneath/from the cold seeps (Clennell et al., 1999; Greinert et al., 2010; Liang et al., 2017; Torres et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these authors observed authigenic ooids within mineralizing studied microbial mats, which perhaps unravel the long-standing and still unsolved mystery of how these prominent carbonate components form. Luis Somoza and co-authors studied the spatial association of Bathymodiolus communities and methane seepage structures at deep-sea mud volcanoes in the Gulf of Cádiz, and elucidated the exact role of microbial symbionts in the bivalves (Somoza et al 2021). A better understanding of these relationships is of uttermost importance, since such symbioses likely have had a lasting impact on the evolution of the involved organisms.…”
mentioning
confidence: 99%